2021
DOI: 10.1097/wnr.0000000000001658
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the antinociceptive effects of serotonin–noradrenaline reuptake inhibitors via sodium channel blockade using the veratrine test in mice

Abstract: Antidepressants exert their analgesic effects by inhibiting the reuptake of noradrenaline. Several antidepressants have been shown to block the sodium channels, which might contribute to their analgesic potency. The aim of this study was to determine whether serotonin-noradrenaline reuptake inhibitors (SNRIs) could produce antinociceptive effects via sodium channel blockade using the veratrine test in mice. Furthermore, the effects of these agents on the veratrine test were examined to elucidate the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…These types of behaviors, such as licking, biting, and scratching, were similar to those observed with injections of formalin, 10) and glutamate 7) in mice. We have shown that not only the sodium channel blockers mexiletine and carbamazepine 9) but also the antidepressants with the potential to inhibit sodium channels duloxetine and venlafaxine 11) suppressed veratrine-induced nociceptive responses. However, the calcium channel alpha-2-delta subunit ligands gabapentin and the T-type calcium channel blocker ethosuximide did not affect veratrine-induced nociception.…”
Section: Introductionmentioning
confidence: 99%
“…These types of behaviors, such as licking, biting, and scratching, were similar to those observed with injections of formalin, 10) and glutamate 7) in mice. We have shown that not only the sodium channel blockers mexiletine and carbamazepine 9) but also the antidepressants with the potential to inhibit sodium channels duloxetine and venlafaxine 11) suppressed veratrine-induced nociceptive responses. However, the calcium channel alpha-2-delta subunit ligands gabapentin and the T-type calcium channel blocker ethosuximide did not affect veratrine-induced nociception.…”
Section: Introductionmentioning
confidence: 99%
“…While milnacipran continues to be an active subject of experimental and clinical studies focusing on chronic pain and major depression [ 9 , 10 , 11 ], it is also being evaluated for other disorders, including cognitive impairment after traumatic brain injury [ 12 ], apnea during Rett syndrome [ 13 ], attention-deficit/hyperactivity disorder [ 14 ] and autism spectrum disorder [ 15 ]. Curiously, there is a paucity of published studies reporting systemic and brain pharmacokinetics of milnacipran in rodents.…”
Section: Introductionmentioning
confidence: 99%